2006
DOI: 10.1007/s00430-006-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori SabA adhesin evokes a strong inflammatory response in human neutrophils which is down-regulated by the neutrophil-activating protein

Abstract: The human pathogen Helicobacter pylori expresses two dominant adhesins; the Lewis b blood group antigen binding adhesin, BabA, and the sialic acid-binding adhesin, SabA. These adhesins recognize specific carbohydrate moieties of the gastric epithelium, i.e. the Lewis b antigen, Le(b), and the sialyl-Lewis x antigen, sLe(x), respectively, which promote infection and inflammatory processes in the gastroduodenal tract. To assess the contribution of each of BabA, SabA and the neutrophil activating protein (HP-NAP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 68 publications
1
23
0
1
Order By: Relevance
“…SMI109 Δ hup was created by transformation of a Δ hup :: kan PCR fragment generated by hup-1 and hup-5 primers, and pAAG178 as template. SMI109 Δ napA was created by transformation of a Δ napA :: kan PCR fragment generated by napA1F and napA1R primers, and pBlue-Δ napA :: kan [78] as template. Deletion of the hup and napA genes was verified by PCR using hup-2 / hup-in and napA2F / napA2R primers, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…SMI109 Δ hup was created by transformation of a Δ hup :: kan PCR fragment generated by hup-1 and hup-5 primers, and pAAG178 as template. SMI109 Δ napA was created by transformation of a Δ napA :: kan PCR fragment generated by napA1F and napA1R primers, and pBlue-Δ napA :: kan [78] as template. Deletion of the hup and napA genes was verified by PCR using hup-2 / hup-in and napA2F / napA2R primers, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…BabA and SabA) have been shown to induce inflammatory cytokines (IL‐6, IL‐8, IL‐12, TNF‐α) and inflammatory cells in the stomach as the host immunoresponse. The inflamed tissue inevitably results in the production of various kinds of ROS, including O 2 − , which causes disorders through severe damage in the stomach (1–12). However, ROS potentially has a role in eliminating microorganisms to defend the cells and tissues in a type of host immunoreaction.…”
mentioning
confidence: 99%
“…In our previous study, we showed that the expression of SabA can enhance the bacterial density in the body when patients lack the BabA receptor, Le b antigen [21]. The binding of H. pylori to sialylated neutrophil receptors through SabA also plays a pivotal role in phagocytosis of the bacteria and the induction of the oxidative burst [28]. Therefore, this study further analyzed whether there is a synergistic effect of the presence of the SabA-sialyl-Le x interaction in the patients infected with different motility strains.…”
Section: Discussionmentioning
confidence: 99%